2014
DOI: 10.2459/jcm.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic stratification of patients with chronic systolic heart failure using biomarkers and Doppler echocardiography

Abstract: A restrictive left-ventricular filling pattern at Doppler echocardiography is the most important prognostic indicator in chronic heart failure patients. Plasma levels of BNP and hsTnI do not provide additional relevant information to identify patients at higher risk of cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Even during systolic heart failure, increased LV filling pressure is closely associated with exercise limitation and is independent of the degree of systolic dysfunction 8. Studies have increasingly indicated that severe diastolic dysfunction (restrictive filling) suggests a worse hemodynamic and clinical status of heart failure as well as increased mortality and heart transplantation rates 22, which is also true for patients undergoing drug treatment 23,24, surgical ventricular restoration 25,26, and CRT 27,28. Using multivariate regression analysis, this study confirmed that severe diastolic dysfunction was an independent factor that influenced the CRT response.…”
Section: Discussionmentioning
confidence: 99%
“…Even during systolic heart failure, increased LV filling pressure is closely associated with exercise limitation and is independent of the degree of systolic dysfunction 8. Studies have increasingly indicated that severe diastolic dysfunction (restrictive filling) suggests a worse hemodynamic and clinical status of heart failure as well as increased mortality and heart transplantation rates 22, which is also true for patients undergoing drug treatment 23,24, surgical ventricular restoration 25,26, and CRT 27,28. Using multivariate regression analysis, this study confirmed that severe diastolic dysfunction was an independent factor that influenced the CRT response.…”
Section: Discussionmentioning
confidence: 99%